Malnutrition increases hippocampal neurogenesis in the immature rat after status epilepticus - Wang, Yan-ling (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2003)
OBJECTIVE: Neurogenesis in the dentate gyrus of hippocampus persists in brain of the immature and adult mammalian including human and it can be regulated by physiological and pathological events including nutritional status and seizures. The present study was designed to investigate the potential effects of malnutrition followed by status epileptics on hippocampal neurogenesis in the immature rat